Empowering Local Communities Through Papaya Dodol Innovation in Gombolharjo - Zulfiqor, Muhammad Riyad; Nasikah, Marshaniswah Vanra; Shidieqy, Zakki Ramdhan Ash; Munir, Muhammad Afifuddin; Nada, Salsabila Fitrotun; Nugroho, Suryo Prakoso Arda; Muhendy, Yayang Nanditya; Salsabila, Azria; Mubarok, Jasmine Aulia; Ramadhani, Shafar Rahma; Nurlatifah, Nova; Ariyati, Tatik; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
Papaya is a nutrient-rich fruit with many health benefits, and Gombolharjo Village has an abundant papaya harvest. The UMP KKN Team group 129 initiated an innovation in processing papaya into papaya dodol to increase the added value of local agricultural products and support MSMEs, along with the creation of packaging and logos for market readiness. The method used is Asset-Based Community Development (ABCD) through five stages: Discovery, Dream, Design, Define, and Destiny. Activities include observation, discussion, design, production, and training with the community. The results show the enthusiasm of residents and the success of papaya dodol production as a new processed product that has the potential to develop MSMEs based on local potential.